Core polarization effects for 13C and 15N nuclei and inelastic longitudinal form factors - Rashed Eman Mosa (E3S Web of Conferences)
In combination with the global set of two-body correlations (FC’s), comprising tensor correlations (TCs) as well as short-range correlations (SRCs), you get light nuclei 13C and 15N inelastic longitudinal C2 form factors and new efficient distance nucleonic system’s two-body density operator in this research. Nucleon-nucleon interactions are described with reference to these correlations incorporating intense short- range repulsion with robust tensor force. Adjusting for core polarization effects. Using these operators, we can observe the shape of transition model with calculating of two-body charge densities (2BCDD’s) at ground states, as subsequent experiment distributions; This transition 13C from ground state(Jiπ, T): (−1/2 , 1/2) to the state (Jfπ, T): (−3/2 , 1/2) with an excitation energy (Ex) = 3.68 Mev and from ground state (Jiπ, T): (−3/2 , 1/2) to the state (Jfπ, T): (−5/2 , 1/2) with an excitation energy (Ex) = 7.55 Mev and 15N nucleus from ground state (Jiπ, T): (−1/2 , 1/2) to the state (Jfπ, T): (−3/2 , 1/2) having an excitation energy (Ex) = 6.32 Mev to calculating the inelastic longitudinally form factors C2 pertaining to the charge density, specifically focusing on the excitation of the mentioned levels.